2018
DOI: 10.7567/jjap.57.03ea06
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on fabrication of memristor and transistor-based neuromorphic devices for high signal processing speed with low power consumption

Abstract: The advanced progress of electronic-based devices for artificial neural networks and recent trends in neuromorphic engineering are discussed in this review. Recent studies indicate that the memristor and transistor are two types of devices that can be implemented as neuromorphic devices. The electrical switching characteristics and physical mechanism of neuromorphic devices based on metal oxide, metal sulfide, silicon, and carbon materials are broadly covered in this review. Moreover, the switching performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 109 publications
0
15
0
Order By: Relevance
“…In 2017, Wang et al analyzed the strategies of recent developments in synaptic functions, conducting filament (CF) control mechanisms, and the correlation among materials. More recently, Hadiyawarman et al in 2018 introduced neuromorphic devices based on carbon, silicon, and other materials. There are also review articles focusing on resistive layer materials.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Wang et al analyzed the strategies of recent developments in synaptic functions, conducting filament (CF) control mechanisms, and the correlation among materials. More recently, Hadiyawarman et al in 2018 introduced neuromorphic devices based on carbon, silicon, and other materials. There are also review articles focusing on resistive layer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance range and threshold voltages are closely related to the materials used in memristor fabrication (Hadiyawarman et al, 2018), which therefore constitute important factors for memristor-based circuit designs. In this paper, the threshold voltages and the resistance ranges are assumed to meet the needs of our design.…”
Section: Memristor Modelmentioning
confidence: 99%
“…Changes in synaptic weight between presynaptic and postsynaptic neurons are known as synaptic plasticity, including short‐term plasticity (STP), long‐term plasticity (LTP), spike‐timing‐dependent plasticity (STDP), etc. [ 9–11 ] It is confirmed that STP is related to computational functions associated with spatiotemporal information, and LTP lays the foundation for memory and learning in the neural system. [ 12 ] And STDP is the learning rule of the Hebbian theory, including asymmetric STDP, symmetric STDP, and anti‐STDP.…”
Section: Introductionmentioning
confidence: 99%